Mathematical models identification in characteristic situations of conduct of the brewery technological complex - Romanov, Mykola; Matsebula, Dmytro; Svitoch, Illia (My University, 2018)
The purpose is to create mathematical models that allow to describe such basic qualitative characteristics of brewing process as quality of production at all stages of the production process, productivity and losses. To pass the passive experiment in the production conditions of the brewery according to the results of which (data of measurements of technological parameters and data of laboratory analyzes) to carry out the identification of mathematical models. In the Matlab, using the least squares method, evaluate the competitive models of certain structures and the parameters of these models based on the criteria: determination, Akaike information criterion, Hawking and Fisher statistics.The use of the above criteria of adequacy allowed us to select the optimal model structures for each situational-significant area in terms of their accuracy and complexity.
Keywords: brewing; fuzzy values of variables; identification of mathematical models; situational-significant zones; пивоваріння; нечіткі значення змінних; ідентифікація математичних моделей; ситуаційно-значущі зони; кафедра автоматизації та комп'ютерних технологій систем управління ім. проф. А.П. Ладанюка